(untitled) (Research, Society and Development, 2023)
Medical education has undergone a series of transformations over the last few decades. Curricular changes increasingly require professionals trained in the integration and handling of new resources. These changes in the way of educating, teaching and instructing are necessary for the complete formation of medical students, since technology is promoting great advances in the medical field. Today, one of the biggest challenges of the medical course, which demands the attention of professors, is preparing students for conscious prescription, especially with regard to antimicrobials, since errors can lead to antimicrobial resistance and even harm to patients. In view of this, the present study aims to develop a manual on antibiotic therapy that is easy to handle and accessible to read to assist teaching. After preparing the material in several stages, the study was carried out with a group of medical students who were studying infectology. The total number of participants was 102 students, where a randomly selected group had access to the manual before applying an objective test 16.66% (N=17). The rate of correct answers for the questions in the group of students who did not access the manual was 52.07% and in the group with access it was 89.80%, a difference of 37.73%. It is concluded that the introduction of digital methodologies as study alternatives is essential, especially nowadays, in which technologies are part of individuals’ lives. Thus, health education could not be left out of this context, needing to evolve along with the globalized postmodern world.